Cross-Cultural Adaptation in Exchange Programs: Sociocultural Challenges for Students and How to Deal with Them - Tanasy, Novalia; Nuraeni, Nuraeni; Aisyah, Sitti; Ali, Muhammad; Ishaq, Musfirah (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
The study addresses the gap in understanding high school exchange students' communication challenges in cross-cultural settings, focusing specifically on Indonesian students in the United States. Unlike existing literature that emphasizes higher education students, this research uniquely explores sociocultural adaptation at the high school level, particularly communication barriers that are often overlooked. Using purposive sampling, six high school students who completed a one-year exchange program in the U.S. were interviewed. Semi-structured interviews enabled a thematic analysis grounded in Braun and Clarke's framework, providing a nuanced view of the students' adaptation process. Findings reveal that participants encountered significant culture shock, stemming from differences in punctuality, etiquette, direct communication, and cultural norms such as part-time work, religious observances, and addressing teachers informally. Linguistic barriers, especially around vocabulary and pronunciation, were intensified by psychological factors like anxiety and self-doubt. Furthermore, non-verbal cues such as eye contact and personal space highlighted distinct communication expectations between Indonesian and American cultures. To navigate these challenges, students adopted coping strategies including assimilation of local customs, proactive communication, and community support. This study’s insights have broader implications for enhancing exchange programs by incorporating targeted support systems that address the communication and adaptation needs of younger students, potentially improving intercultural competence and easing the transition for future exchange participant.